2010
DOI: 10.3171/2010.6.jns10346
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cigarette smoking addiction after posterior cingulate damage

Abstract: The authors describe the case of a 35-year-old woman with a history of an addiction to cigarette smoking who presented with an intracerebral hemorrhage from a ruptured arteriovenous malformation. The patient reported an immediate and complete disruption of her addiction to cigarette smoking following her stroke. Structural MR imaging revealed a lesion of the posterior cingulate cortex. Neuropsychological tests showed intact cognitive functioning. This observation suggests that the posterior cingulate cortex ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Prior work has linked increased posterior cingulate activation with increased craving (Franklin et al, 2007), suggesting that this region is sensitive to disruption by nicotine. In fact, one case study suggested that a lesion to posterior cingulate disrupted nicotine addiction altogether (Jarraya et al, 2010). In oculomotor studies, posterior cingulate, similar to anterior cingulate, has been noted to contribute to active saccadic inhibition (Brown et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has linked increased posterior cingulate activation with increased craving (Franklin et al, 2007), suggesting that this region is sensitive to disruption by nicotine. In fact, one case study suggested that a lesion to posterior cingulate disrupted nicotine addiction altogether (Jarraya et al, 2010). In oculomotor studies, posterior cingulate, similar to anterior cingulate, has been noted to contribute to active saccadic inhibition (Brown et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced functional connectivity between putamen and cingulate cortex was found to be correlated with nicotine addiction severity [27]. A recent case study reported that a woman with a history of an addiction to cigarette smoking reported an immediate and complete disruption of her addiction to cigarette smoking following after posterior cingulate damage [28]. This observation suggests that the posterior cingulate cortex may also play an important role in the addiction to cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with some previous findings. For example, in one study, a stroke that produced a lesion of the PCC resulted in an immediate cessation of smoking (40). More generally, studies of addicted smokers have shown increased activity in PCC and cerebellum in comparison with those of nonsmokers (12,17,19).…”
Section: Discussionmentioning
confidence: 99%